GAMBARAN KARAKTERISTIK PENGAWAS MINUM OBAT (PMO) ANTI TUBERKULOSIS PADA ANAK DENGAN TUBERKULOSIS DI RSUD AJIBARANG - Isabella Josephine Nurwina; Noor Yunida Triana; Siti Haniyah (Bajang Institute, 2024)
Pulmonary tuberculosis (pulmonary TB) is an infectious disease caused by tuberculosis germs (Mycobacterium tuberculosis). This disease is still a global health problem, one of the efforts to support the success of taking medication is through the role of the Medicine Taking Supervisor (PMO). A medication taking supervisor (PMO) is someone who lives near the sufferer's house or who lives in the same house as the sufferer so he can supervise the sufferer until they actually swallow the medication every day so that drug withdrawal does not occur and this is done voluntarily. This research aims to characteristict of supervisors taking anti-tuberculosis medication in children with tuberculosis at Ajibarang Regional Hospital. This research uses quantitative methods with a descriptive design. The sample involved in this research was 102 respondents taken using total incidental sampling techniques. The research results showed that based on the characteristics of the respondents, the majority were aged 18 - 35 years, 60 respondents (58.8%), 84 respondents (82.4%), 84 respondents (82.4%), 49 respondents (48%), not working at least high school. people (59.8%). The relevance is that if the PMO has a good or supportive role and has training, the cure rate or treatment success will increase. It is hoped that future researchers can carry out further research, by deepening the role of PMO in patients. It is hoped that the Ajibarang Regional Hospital will have PMO competence in order to increase the success rate of pediatric TB treatment at the Ajibarang General Hospital